Análisis de la efectividad del procedimiento sumario en los juicios de demarcación de linderos en casos de oposición a los procedimientos voluntarios. - Silva Moreno Gissela Alexandra (2025)
The present research paper titled "Analysis of the Effectiveness of the Summary Procedure in Boundary Demarcation Trials in Cases of Opposition to Voluntary Procedures" focuses on the judicial and notarial procedure in boundary demarcation in case of opposition. Its objective is to analyze the procedures established in Ecuadorian legislation to resolve disputes over boundary demarcation, with special emphasis on the summary procedure in cases of opposition to voluntary procedures established under the current legal framework: the judicial procedure, regulated by the Organic General Code of Processes (COGEP); and the notarial procedure, regulated by the Notarial Law. The analysis is aimed at reviewing the role of the Notary regarding the authority granted by law in boundary demarcation procedures, as this legal provision transfers matters of voluntary jurisdiction to the Notary, procedures that were historically handled by the judicial bodies of the Judicial Branch in civil matters. Additionally, a review is made of boundary demarcation cases in opposition handled in the Judicial Units, focusing on identifying the differences, similarities, advantages, and disadvantages of each procedure, as well as analyzing their effectiveness in resolving boundary demarcation conflicts when there is opposition between the parties. A key point is that, as a voluntary jurisdiction procedure, it becomes contentious due to various circumstances, leading to the judicialization of the case. Through a historical analysis of this legal figure of boundary demarcation in opposition within the procedural scope, the evolution of this matter within the jurisdictional sphere will be determined, noting that traditionally, the resolution of such conflicts in judicial procedures has been handled in courts. Furthermore, these processes 6 were often long, costly, and at times inefficient, which led to dissatisfaction among the affected parties. With the modernization of Ecuadorian legislation, the Notarial Law incorporated an alternative mechanism for resolving these conflicts through the notarial route, allowing a more agile and less formal process, although with certain limitations in cases of opposition between the parties. The coexistence of both procedures has raised questions about which is more suitable under different circumstances, especially when disagreements arise among the interested parties. This study uses descriptive and explanatory research. The descriptive research focuses on detailing the characteristics of Articles 332.2 of the COGEP and 18.21 of the Notarial Law, establishing how each regulation governs the boundary demarcation procedure and its application in practice. On the other hand, the explanatory research seeks to analyze the causes and consequences of the choice between the judicial and notarial procedures in boundary demarcation cases when there is opposition, evaluating the effects of this choice in terms of speed, costs, and effective conflict resolution. The development of this paper aims not only to describe and explain the judicial and notarial procedures in boundary demarcation but also to provide a critical evaluation of their effectiveness in practice. Keywords: Boundary demarcation, Property conflict, Notarial Law, Opposition between parties, Voluntary jurisdiction, Controversy..